Ojämlika arbetsplatser : Hierarkier, diskriminering och strategier för jämlikhet (Kriterium, 2021)
In this research anthology, inequality in Swedish working life in a Sweden marked by increased inequality, is studied. Racialised inequality, racism and discrimination in individual workplaces are focused, but inequalities based on class and gender are also studied. The concept of inequality regime is used by several of the authors to analyse work organizations. The workplaces studied are found in different sectors, not least in healthcare. The book also includes contributions that provide comparative international perspectives and studies of the development of inequality over time. The anthology contains 12 chapters based on empirical studies of working life, one chapter that analyses working life inequality from a political theory perspective, an introduction and a closing chapter that frames and draws conclusions from the different studies, as well as an afterword. The authors are 22 researchers from different social science disciplines.